Impact of hole transport layer on the performance of all-inorganic tin (Sn) based perovskite solar cells. Issue 1 (March 2021) - Roy, P; Dongre, Y K; Tiwari, S; Chaturvedi, D; Khare, A
Abstract: The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has shown vast increment from 3.81% to 25.5% within a decade. Despite the fast progress and many advantages, these cells are facing an issue of toxicity and poor device stability. In this work, we deal with the issue of toxicity by using Tin (Sn) instead of Lead (Pb). The PSCs are simulated using Solar Simulator Capacitor (SCAPS-1D version 3.3.07) software. We used all-inorganic, lead free material, Cesium Tin–Germanium Tri-iodide (CsSn0.5 Ge0.5 I3 ) as an absorber material. We further investigate the influence of hole transport layer (HTL) on the performance of Sn based PSCs. Simulation and analysis of following CsSn0.5 Ge0.5 I3 based PSC devices have been done: using (i) HTL free configuration (ii) inorganic HTL and (iii) organic HTL. The simulated cells are in planar n-i-p architecture. This work depicts the fact that Sn based PSCs have a potential to serve as high performance solar cells. The results signifies the impact of HTL on the performance of PSCs, in this study, we also suggest alternatives to the widely used HTM (Spiro-OMeTAD) that not only produce comparable photovoltaic performance but also are cost effective. We also analyse the influence of using various metal cathodes on the simulated cell. The result suggests that presence and type of HTM is having an impact on the contact selection criteria. The influence of HTL thickness variation on the performance of the PSCs are also studied.